Actantial Variation in Santiago del Estero Quichua: the Applicatives (Part I) - Albarracín, Lelia Inés (2021)
In the dialectal variety of Quechua spoken in the province of Santiago del Estero, Argentina, there are basically two mechanisms that allow the increase of verbal valence: through causatives or applicatives. Although there is an exhaustive description of the mechanisms of verbal valency increase by means of causatives and also an extensive explanation of the functioning of the so-called «transitional suffixes», there are no further details regarding their use with certain verbs in applicative structures and without describing this operation as a mechanism of valential adjustment. Based on recent and still ongoing research, we are rethinking these mechanisms, reanalyzing suffixes already described but now from this new perspective. In this paper, we present an advance of the results obtained so far.